O ensino de ciências na perspectiva da alfabetização científica e tecnológica e formação de professores: diagnóstico, análise e proposta - Lopes, Werner Zacarias (2014)
This dissertation was developed among a group of Initial Years teachers of municipal schools from Alegrete /RS, in 2012, and it is focused on the diagnosis, analysis and development of a Science Teaching approach under the perspective of Scientific Literacy (SL) with the focus on Science, Technology and Society (STS). The methodological approach was qualitative, of comprehensive-interpretative nature, and the action-research was the investigation support, divided into two manuscripts. The first is characterized by the diagnosis of the teachers perception about the SL perspective with the focus on STS, when a questionnaire was used with open and closed questions. 58 teachers participated in this research. Results showed that the teachers understand the importance of the topic, but they are not prepared to evolve this theme in class. Besides, a great number of educators do not explicit in their practices the way that this SL perspective with the focus on STS may contribute do the Science Teaching. Likewise, when they were asked about the fact that their curriculum does not contemplate the SL with the focus on SIS, they mentioned that this topic does not contemplate this focus on their formation (68,96%), as well as 96,56% of these teachers do not have courses or graduations about the thematic of SL in STS. The second manuscript is characterized by an analysis of how the continued formation based on SL with the focus on STS impacted a group of teachers of Initial Years. 40 teachers participated, and 12 finalized. A questionnaire with open questions, participant observation and project analysis, besides a field journal, were used as tools to collect data. Results showed that teachers who participated at this research have a conceptual, linear and traditional perception of the Science subjects. However, at the projects reports, 66,67% of the teachers showed a vision of real, interdisciplinary and contextualized Science. With the evidenced results, we realized that the teacher s formation had a positive impact at the understanding about the Science Teaching construction. Thus, we hope that this dissertation may contribute with future educational actions, encouraging the development of problematizing methodologies, that are constituted as an important tool at interdisciplinary projects construction, that aim at an education more contextualized and closer to students reality.